ANALYSIS OF MATHEMATIC REASONING ABILITY THROUGH OPEN-ENDED PROBLEMS IN CLASS XII ACCOUNTING 1 VOCATIONAL SCHOOL, DIPONEGORO SALATIGA STUDY YEAR 2020/2021 - Annisa Puspita Fanhary (Program Studi Tadris Matematika IAIN Salatiga, 2019)
AbstractThe purpose of this study was to analyze the mathematical reasoning abilities of students in class XII Accounting 1 SMK Diponegoro Salatiga, the efforts of teachers in maximizing the mathematical reasoning abilities of students in class XII Accounting 1 at SMK Diponegoro Salatiga, and the efforts of the teacher in overcoming problems with the students' low mathematical reasoning abilities. The method used in this research is to use a qualitative approach. Data collection in this study was a written test and interviews. The test was conducted to determine the students' mathematical reasoning abilities by using 3 open-ended questions in the form of descriptions. Interviews were conducted to find out in depth the mathematical reasoning abilities of students in solving math problems which were followed by 6 out of 29 students who were selected based on the students' abilities, namely 2 students with high abilities, 2 students with moderate abilities and 2 students with low abilities. The results of the study reveal that: (1) high-ability students meet the indicators of presenting mathematical statements orally, in writing, pictures and diagrams; submit allegations; manipulating mathematics; compile evidence, provide reasons / evidence for the correctness of the solution; draw a conclusion; and check the validity of an argument. Students who are able to meet the indicators present mathematical statements orally, in writing, pictures and diagrams; submit allegations; and manipulate math. Low ability students meet the indicators of presenting mathematical statements orally, in writing, pictures and diagrams; and put forward allegations. (2) the efforts of the teacher in maximizing the mathematical reasoning abilities of students in class XII Accounting 1 SMK Diponegoro Salatiga by enriching and remedials. (3) the efforts of the teacher in overcoming students' low mathematical reasoning abilities by conducting peer tutoring. Keywords: Ability Analysis, Mathematical Reasoning, Open-ended Problems.